A rare case of partial trisomy 8q24.12-q24.3 and partial monosomy of 8q24.3: Prenatal diagnosis and clinical findings - Farcas, Simona; Erdelean, Dragos; Anne-Elise Szekely, Flavia; Navolan, Dan; Andreescu, Nicoleta; Cioca, Andreea (Taiwanese journal of obstetrics & gynecology, 2019)
We describe a rare case of “pure” 8q duplication diagnosed prenatally by conventional karyotyping, that was further characterized by array comparative genomic hybridization (aCGH). A 39-year-old, primigravida woman underwent amniocentesis at 23 weeks of gestation because of an abnormal second trimester maternal serum screening for Down syndrome. Conventional cytogenetic analysis demonstrated a karyotype of 46,XX,der(8) (q24.12q24.3) and aCGH identified a duplication of approximately 27 Mb, affecting the distal region of chromosome 8q24.12-q24.3. Parenteral karyotype of both parents was normal and excluded familial translocation or other rearrangements. Although prenatal ultrasound examination showed multiple anomalies the parents decided to keep the pregnancy. The baby was born at 38 weeks of gestation, with an Apgar score of 2. The evolution was unfavorable, and he died within the first 24 h of birth. Molecular investigations contribute to a more accurate characterization of the patients with these rare duplication, but also for estimating their prognosis.